Soil Erosion Aspects in Agriculture - Imdad, Sumbal (Delve Publishing, 2019)
Soil Erosion Aspects in Agriculture explains carious dimensions of agriculture sector with an extensive information on soil erosion and its aspects in agriculture sector. It includes the meaning of soil degradation, water erosion, wind erosion and factors influencing these three types of erosions. Provide the reader with an insight into the development of various resources that would help in getting rid of the problems arising from soil erosion. This would help in achieving sustainable practices for cultivation.